Stress and Glucose metabolism: A Review - Nirupama R; Barathi Rajaraman; Yajurvedi HN (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2018)
Stress is an inescapable fact of life. The perceived stress induces endocrine alterations characterized by the activation of hypothalamo-pituitary-adrenal axis and sympathetic adreno-medullary axis. The glucocorticoids and catecholamines which are secreted in response to stress induce variations in the physiology and behavior that help the individual to adapt to changing demands of the body. Glucocorticoids are known to play a central role in inducing the stress related pathophysiology. These hormones induce hypermetabolism in order to cope up with the increasing energy demands of the body. However when the stress is persistent the body adapts itself to continuous demands and starts regulating the metabolism at higher levels than the normal, termed as allostasis. This overwhelming load on the body will predispose the individual for the development of diseases. This mini-review focuses on long term chronic stress induced alterations in glucose metabolism and development of insulin resistance and glucose intolerance as a result of long term allostatic regulation.